Prospero and Caliban the psychology of colonization - Mannoni, Octave (Ann Arbor University of Michigan Press, 1990)
A classic in psychological ethnography and the history of colonialism
Translation of : Psychologie de la colonisation.
Keywords: Ethnology -Madagascar.